The Effect of Training Results Perception on Individual Work Performance of Employee Moderated by Intrinsic and Extrinsic Motivation - Hidayah Turachma; Hidajat Hendarsjah (Jurnal Manajemen Indonesia, 2021)
This study aims at examining the effect of training results perceptions on individual work performance of employee, and intrinsic and extrinsic motivation serving as moderation strengthening that effect. T his study was quantitative research selecting 453 samples out of 1.311 population from PT KAI’s employees in which they are executive officer. The data collection was done using a close questionnaire with Likert scale 1-5. All valid and reliable instruments were assessed through Factor Analysis and Cronbach's Alpha Analysis. Hypothesis testing is carried out using Hierarchical Regression Analysis by including the Multicollinearity test as a prerequisite for analysis. The study results showed that training result perceptions and extrinsic motivation simultaneously or partially have a positive and significant effect on individual work performance of employee, but intrinsic motivation have no significant effect. Intrinsic or extrinsic motivation does not moderate or strengthen the relationship between training result perceptions and individual work performance of employee. The three independent variables are not related to each other. PT KAI’s employees, especially those in executive position, are more oriented towards extrinsic results than intrinsic ones. The implication for PT KAI is that to improve the individual work performance of its employees, the organization can focus on improving training, external motivation or both. It depends on the vision, long-term goals, and resources of PT KAI.